PESANTREN: LEMBAGA PENDIDIKAN SEKALIGUS KQMUNITAS ISLAM YANG KHAS, SEBUAH AKULTURASI BUDAYA: Pesantren (Islamic boarding school), traditional, Islamic, cultural acculturation. - Achmad Qomaru Zaman (Universitas PGRI Adi Buana, 2011)
Pesantren (Islamic Boarding School) is a traditional institution for Muslims, founded among 13th-15th century, which teaches the importance of religious morality to guide everyday behavior. In its development, the schools not only teach religious sciences, but also general science. Instead of educational and social institution, Pesantren is as well as religious broadcasters institutions. The students' community actually is an Islamic society which consists of groups of students bound together by tradition and systems, custom and law